2020
DOI: 10.2147/copd.s254172
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>Lycium barbarum</em> Polysaccharide Inhibited Hypoxia-Inducible Factor 1 in COPD Patients</p>

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a chronic airway inflammatory disease characterized by irreversible airflow obstruction. Pathogenic mechanisms underlying COPD remain largely unknown. Objective: The current study was designed to explore serum concentration of hypoxiainducible factor 1α (HIF-1α) in stable COPD patients and the potential effect of Lycium barbarum polysaccharides (LBP) on HIF-1α protein expression. Methods: Serum HIF-1α was quantified by ELISA in 102 stable COPD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In recent years, natural bioactive compounds have attracted extensive attention as anticancer drugs because of their high therapeutic value and low systemic toxicity ( 39 ). For example, GQZ was reported to have therapeutic effects on kidney injury, lung injury and aging related diseases ( 14 , 40 , 41 ). GQZ extract enhanced the radiation of Lewis lung cancer acute hypoxic cells, although the relevant active ingredient and its mechanism of action have not yet been clearly determined ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, natural bioactive compounds have attracted extensive attention as anticancer drugs because of their high therapeutic value and low systemic toxicity ( 39 ). For example, GQZ was reported to have therapeutic effects on kidney injury, lung injury and aging related diseases ( 14 , 40 , 41 ). GQZ extract enhanced the radiation of Lewis lung cancer acute hypoxic cells, although the relevant active ingredient and its mechanism of action have not yet been clearly determined ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The components of LB can treat a variety of lung related diseases. For example, lycium barbarum polysaccharide (LBP) can alleviate the symptoms of dyspnea in patients with stable COPD by reducing hypoxia-inducible factor 1- α (HIF-1α) ( 14 ), and can improve symptoms of allergic asthma by reducing lung lesions, improving airway inflammation and regulating intestinal flora ( 15 ). In addition, the combination of LBP and Lak/IL-2 has been found to prolong the life span and improve the quality of life of patients with lung cancer ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, multiple conditions, such as cancer, aging, fatigue, colitis, stroke, diabetes, Alzheimer's disease, and glaucoma, have been proven to benefit from LBP (118). Chen et al (119) demonstrated that oral LBP (5 mg/mL, 100 mL twice daily for 2 weeks) improved COPD symptoms and significantly decreased blood HIF-1a levels. In this study, oral LBP elicited moderate adverse effects, including constipation, dry mouth, inflamed gums, and gastrointestinal reactions.…”
Section: Lycium Barbarum Polysaccharidesmentioning
confidence: 99%